Jatropha curcas oil characterization and its significance for feedstock selection in biodiesel production - Mohammed , Nurudeen Ishola; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (IACSIT Press, Singapore, 2014)
Over time, the quest for alternative fuel devoid of environmental degradation has intensified research on biodiesel synthesis from diverse feedstock. Biodiesel is an environmental friendly alternative liquid fuel that can be used in any diesel engine with little or no engine modification. There has been kindled interest in vegetable oils consideration for making biodiesel on account of its less polluting nature and benefits of its renewability compared to fossil diesel fuel. Once biodiesel is accorded the needed support and incentive, it stands to offer enormous benefits for the environment and the local population in terms of employment opportunity as well as provision of modern energy carriers for the use of rural communities. Moreover, non-edible oil such as jatropha curcas oil has experienced ongoing inquiry due to food-energy feud of some edible oils utilized as feedstock in biodiesel synthesis. In producing biodiesel which can be economically viable, it is imperative that the characteristic features of the feedstock are determined in order that all the available alternative approaches to produce the fuel are weighted before there can be any consideration for a particular method. In this paper, three jatropha curcas oil species were characterized and the implication of the various characteristic features in choosing the feedstocks for consideration in biodiesel synthesis are evaluated and discussed.